Efeitos da judicialização das escolhas regulatórias complexas no setor elétrico brasileiro que impactam as liquidações da CCEE - Marques, Lara Cristina Ribeiro Piau (2018)
The legitimacy and autonomy of the decisions that guide and define the regulatory action are supported by a regulatory model designed by the Federal Constitution, laws and principles that configure the so-called regulatory framework. It is therefore within the perimeter of the regulatory framework that the decisions and regulatory choices of the Brazilian Electricity Sector must be defined and adopted. These presuppose clear rules, predictability and absence of external interference, always observing the need to preserve an environment that reconciles the investor's confidence and the guarantee of the adequate provision of the service. But the impact and scope of regulatory choices have been increasingly submitted to the Judiciary. Based on the intense judicialization of regulatory choices in the Brazilian Electricity Sector, which impact the settlement and accounting of energy purchase and sale contracts, carried out by the Electric Energy Trading Chamber (CCEE), this work pretend to identify, through the study of CNPE 03/2013 and GSF cases, the factor or the element that is provoking the migration of the discussion of these subjects, of preponderant technical-regulatory nature, to the Judiciary Power. The hypothesis is that the judicialization is responsive and reactive, and stems from the attempt to avoid imbalance and financial burden imposed on agents, with changes in contractual conditions and business plan, by regulatory choices out of alignment with the logic and regulatory structure.